131 Migrants' work-related injuries in the New Zealand media: Hidden voices, missed opportunities. (20th November 2022) - Radka, Kelly; Ergler, Christina; Wyeth, Emma; Derrett, Sarah
Abstract : Background: In 2020, migrants comprised 28.7% of Aotearoa/New Zealand's (NZ) population. Statistics NZ (2021) reports work-related injury claims are disproportionately high amongst workers reporting 'Middle Eastern, Latin American, African, & other ethnicities'. Media analyses have highlighted the social construction of occupational injuries in other countries. Little appears to be known regarding the scope and nature of mainstream media's (MSM) representations of migrants' work-related injuries in NZ. Aims: To identify, qualitatively describe, and interpret, NZ MSM representations of migrants' work-related injury experiences and outcomes (2007 – 2021). Methods: Articles have been retrieved from the top ten newspapers and top three news websites in NZ, aligning with identified NZ's news-seeking preferences. Thematic analysis of MSM news articles is nearing completion. Results: A total of 26 eligible news articles were identified, reflecting the paucity of MSM attention to migrant work-related injuries. Additionally, few articles reported occupational injuries from migrants themselves; none referenced female migrants. The issue of migrants' occupational injuries included 'normalisation' of work-related injuries and migrant worker exploitation as 'a hidden problem'. Conclusion: Through the absent voices of migrants, and women specifically, MSM is not facilitating attention to injury experiences of these groups. MSM has the potential to illuminate how migrants' occupational injuries require attention across spaces, from workers to employers, industries and structurally, suggesting the need to reimagine the role of MSM in this regard. Learning outcomes: Gain an increased understanding of media analysis vis-à-vis work-related injuries Learn about the framing of occupationally injured migrants in NZ media